Review of formulae for efficiency calculation of noise barriers in streets - Шевченко, Ю.С. (Proceedings of National Aviation University (archive), 2010)
Analysis of principal formulae for calculation of diffraction effects on the top edge of noise barrier and interference effects of sound waves after reflection from impedance surfaces was done. Main criteria of noise barriers efficiency assessment were considered. Model for calculation of building façade impact was analyzed. Assessment of building façade impact on sound field formation on the street was done.